2019
DOI: 10.1108/jcms-06-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Do Fama–French common risk-factor portfolio investors herd on a daily basis? Implications for common risk-factor regressions

Abstract: Purpose The purpose of this paper is to examine whether Fama–French common risk-factor portfolio investors herd on a daily basis for five developed markets, namely, Europe, Japan, Asia Pacific ex Japan, North America and Globe. Design/methodology/approach To examine the herd behavior of common risk-factor portfolio investors, this paper utilizes the cross-sectional absolute deviations (CSAD) methodology, covering a daily data sampling period of July 1990 to January 2019 from Kenneth R. French-Data Library. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Post-Markowitz research has shown that the use of variance as a risk factor has shortcomings that cause the traditional tools in forecasting to be criticized (Raei et al, 2020). Studies such as Herberger and Reinle (2020); Senarathne (2019); Gupta et al (2014), and Ince and Trafalias (2007) state that using traditional forecasting tools and methods has a high error rate and they have poorer performance compared to newer methods and nonlinear models. In this study, one of the artificial intelligence methods called support vector machine, along with one of the most widely used algorithms in this field, the adaptive neural fuzzy inference system, are examined to predict the most desirable stock portfolio because the goal is to choose the appropriate forecasting method in selecting the desired portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…Post-Markowitz research has shown that the use of variance as a risk factor has shortcomings that cause the traditional tools in forecasting to be criticized (Raei et al, 2020). Studies such as Herberger and Reinle (2020); Senarathne (2019); Gupta et al (2014), and Ince and Trafalias (2007) state that using traditional forecasting tools and methods has a high error rate and they have poorer performance compared to newer methods and nonlinear models. In this study, one of the artificial intelligence methods called support vector machine, along with one of the most widely used algorithms in this field, the adaptive neural fuzzy inference system, are examined to predict the most desirable stock portfolio because the goal is to choose the appropriate forecasting method in selecting the desired portfolio.…”
Section: Introductionmentioning
confidence: 99%